STRATEGI MENGELOLA APLIKASI DAN PENDAPATAN OJEK ONLINE TERHADAP KESEJAHTERAAN KELUARGA Studi kasus Ojek Online di pangkalan Mega Bekasi Hypermall - Atia Mundia; Rustomo Rustomo; Taryanto Taryanto (JURNAL ILMIAH EDUNOMIKA, 2024)
Technological developments make information grow rapidly among the public. On the one hand, this can educate, but on the other hand, it can be detrimental if people are not selective in responding to this information. Since the beginning, the issue and at the same time the reality of an easy job, namely being a motorbike taxi driver with online facilities, has been phenomenal. Until now, Gojek claims to have 200 thousand drivers throughout Indonesia. In Surabaya alone, there are almost 20,000 motorbike taxi drivers. The objectives of the research include (1) To find out the strategy for managing online motorcycle taxi applications on family welfare, (2) To find out how online motorcycle taxi income is sufficient for family welfare, (3) To find out how much influence managing online motorcycle taxi applications and income has on family welfare. This research will be built with an experimental research design using a descriptive quantitative approach, with survey research methods. Data collection techniques using interviews from the total population of online motorcycle taxi drivers at the Mega Bekasi Hypermall base, numbering 30 – 40 motorcycle taxi drivers. The results of the discussion are that the strategy for managing online motorcycle taxi applications can increase the income of online transportation drivers by having a good rating, so that drivers get more customers or passengers, this will be directly proportional to the income earned by the driver. The strategy of managing online motorcycle taxi income can improve the welfare of online transportation drivers by bringing their own provisions for motorcycle taxi drivers. By looking at the results of the analysis that has been carried out, it can be concluded that managing the application well and managing online motorcycle taxi income can improve family welfare.